Genome-Wide Association Study of Kernel Traits Using a 35K SNP Array in Bread Wheat (Triticum aestivum L.) - Wang, Peng; Tian, Tian; Ma, Jingfu; Liu, Yuan; Zhang, Peipei; Chen, Tao; Shahinnia, Fahimeh; Yang, Delong (Frontiers in Plant Science, 2022)
Kernel size and weight are crucial components of grain yield in wheat. Deciphering their genetic basis is essential for improving yield potential in wheat breeding. In the present study, five kernel traits, including kernel length (KL), kernel width (KW), kernel diameter ratio (KDR), kernel perimeter (KP) and thousand-kernel weight (TKW), were evaluated in a panel consisting of 198 wheat accessions under six environments. Wheat accessions were genotyped using the 35K SNP iSelect chip array, resulting in a set of 13,228 polymorphic SNP markers that were used for genome-wide association study (GWAS). A total of 146 significant marker-trait associations (MTAs) were identiﬁed for five kernel traits on 21 chromosomes (-log10(P) ≥ 3), which explained 5.91-15.02% of the phenotypic variation. Of these, 12 stable MTAs were identiﬁed in multiple environments, and six superior alleles showed positive effects on KL, KP and KDR. Four potential candidate genes underlying the associated SNP markers were predicted for encoding ML protein, F-box protein, ethylene-responsive transcription factor, and 1,4-α-glucan branching enzyme. These genes were strongly expressed in grain development at different growth stages. The results will provide new insights into the genetic basis of kernel traits in wheat. The associated SNP markers and predicted candidate genes will facilitate marker-assisted selection in wheat breeding.